Health Information Exchange Use (1990-2015): A Systematic Review. Issue 1 (7th December 2017) - Devine, Emily Beth; Totten, Annette M.; Gorman, Paul; Eden, Karen B.; Kassakian, Steven; Woods, Susan; Daeges, Monica; Pappas, Miranda; McDonagh, Marian; Hersh, William R.
Background: In June 2014, the Office of the National Coordinator for Health Information Technology published a 10-year roadmap for the United States to achieve interoperability of electronic health records (EHR) by 2024. A key component of this strategy is the promotion of nationwide health information exchange (HIE). The 2009 Health Information Technology for Economic and Clinical Health (HITECH) Act provided significant investments to achieve HIE. Objective: We conducted a systematic literature review to describe the use of HIE through 2015. Methods: We searched MEDLINE, PsycINFO, CINAHL, and Cochrane databases (1990 – 2015); reference lists; and tables of contents of journals not indexed in the databases searched. We extracted data describing study design, setting, geographic location, characteristics of HIE implementation, analysis, follow-up, and results. Study quality was dual-rated using pre-specified criteria and discrepancies resolved through consensus. Results: We identified 58 studies describing either level of use or primary uses of HIE. These were a mix of surveys, retrospective database analyses, descriptions of audit logs, and focus groups. Settings ranged from community-wide to multinational. Results suggest that HIE use has risen substantially over time, with 82% of non-federal hospitals exchanging information (2015), 38% of physician practices (2013), and 17-23% of long-term care facilities (2013). Statewide efforts, originally funded by HITECH, varied widely, with a small number of states providing the bulk of the data. Characteristics of greater use include the presence of an EHR, larger practice size, and larger market share of the health-system. Conclusions: Use of HIE in the United States is growing but is still limited. Opportunities remain for expansion. Characteristics of successful implementations may provide a path forward.